2017
DOI: 10.1038/s41564-017-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of NLRP3 in chikungunya disease reveals a role for inflammasomes in alphavirus-induced inflammation

Abstract: Mosquito-borne viruses can cause severe inflammatory diseases and there are limited therapeutic solutions targeted specifically at virus-induced inflammation. Chikungunya virus (CHIKV), a re-emerging alphavirus responsible for several outbreaks worldwide in the past decade, causes debilitating joint inflammation and severe pain. Here, we show that CHIKV infection activates the NLRP3 inflammasome in humans and mice. Peripheral blood mononuclear cells isolated from CHIKV-infected patients showed elevated NLRP3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 49 publications
15
53
0
1
Order By: Relevance
“…Importantly, these data account to explain our previous demonstration that NLRP3 inhibitors can interfere with the pathogenesis of CHIKV virus (24).…”
Section: Systems Biological Approaches Can Provide Comprehensive and supporting
confidence: 67%
See 2 more Smart Citations
“…Importantly, these data account to explain our previous demonstration that NLRP3 inhibitors can interfere with the pathogenesis of CHIKV virus (24).…”
Section: Systems Biological Approaches Can Provide Comprehensive and supporting
confidence: 67%
“…As the inflammasome-related genes are exclusively up-regulated in CHIKV infection and was described before in this context (24), we decided to provide a deeper proof-of-concept related to these findings. The murine bone marrow-derived macrophages were infected with CHIKV virus and the readouts of the inflammasome activation were measured.…”
Section: Comparing Chikv Signature With Rheumatoid Arthritis and Dengmentioning
confidence: 79%
See 1 more Smart Citation
“…The typical vector responsible for transmission of CHIKV was Aedes aegypti , but a mutation in the viral envelope led to enhanced replication in the Aedes albopictus mosquitos present in temperate regions, potentially expanding the range of transmission (Tsetsarkin et al, 2007). CHIKV-induced arthropathy is due to viral replication and the ensuing host inflammatory response (Suhrbier et al, 2012), including inflammasome activation (Chen et al, 2017) and T-cell mediated pathogenesis (Amdekar et al, 2017). …”
mentioning
confidence: 99%
“…Recently, it was shown that treatment of murine macrophages with halofuginone leads to sequestration of IL-1β mRNA into translationally inactive riboclusters, thereby suppressing the inflammasome (Battu et al, 2018). Since inflammasome activation plays a significant role in CHIKV pathogenesis (Chen et al, 2017), halofuginone may be efficacious against both viral replication and the subsequent arthralgia-inducing host inflammation. Furthermore, halofuginone downregulates NF-κB signaling pathway (Luo et al, 2018), which contributes to DENV-induced hemorrhage (Lin et al, 2014).…”
mentioning
confidence: 99%